2021
DOI: 10.3389/fpubh.2021.747371
|View full text |Cite
|
Sign up to set email alerts
|

Dental Caries and Associated Factors in 3–5-Year-Old Children in Guizhou Province, China: An Epidemiological Survey (2015–2016)

Abstract: Objective: This study aimed to explore the factors influencing dental caries among 3–5-year-old children in Guizhou Province and the interrelationship between these factors using structural equation modeling, while providing theoretical references to improve the prevention and control strategy.Materials and Methods: A total of 1,291 children aged 3–5 years in Guizhou Province were selected by a multistage stratified and whole group random sampling to examine the caries prevalence in whole-mouth deciduous teeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…Tooth decay was reported among 184 of children (61.3%) whereas gingivitis was noted among 92 of children (30.7%) followed by toothache 22.3% and others 17.7% Table (1). A consistent result in China by Guan et. (2021) reported that the caries prevalence was 63.1% of a total 1,291 children aged 3-5 years.…”
Section: Discussionsupporting
confidence: 57%
“…Tooth decay was reported among 184 of children (61.3%) whereas gingivitis was noted among 92 of children (30.7%) followed by toothache 22.3% and others 17.7% Table (1). A consistent result in China by Guan et. (2021) reported that the caries prevalence was 63.1% of a total 1,291 children aged 3-5 years.…”
Section: Discussionsupporting
confidence: 57%
“…The present study revealed that the caries prevalence and the mean dmft of ECC among children aged 3-5 years in Xiangyun (74.3%, 4.9) were much higher than the national average score (62.5%, 3.35) reported by the fourth national epidemiological survey ( 5 ). Moreover, the ECC prevalence in this sample is not only higher than results in recent surveys of relatively developed regions, such as Guangdong (68.3%) ( 12 ), Shanghai (between 29.38% and 50.25% among 3–5-year old children) ( 15 ), and Zhejiang (70.4%) ( 14 ), but also developing regions, such as Weifang (between 46.4 and 63.1% among 3–5-year old children) ( 16 ) and Guizhou (63.1%) in China ( 13 ). These results indicate that dental caries is a severe and urgent problem among children in Xiangyun, China.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, both higher parental education level and family income were related to the notably higher frequency of brushing teeth and parental supervision of brushing teeth, a higher proportion of children using fluoride toothpaste and receiving fluoride varnish, and better knowledge about whether decayed primary teeth need treatment and teeth need protections ( Tables 4 , 5 ). In general, parents with higher socioeconomic status will have much more opportunities to access health information, preferentially attend public dental services, and receive oral health advice ( 13 , 21 ), which, in turn, can contribute to caries prevention for children. Nevertheless, high socioeconomic status did not correlate with good dietary habits for caries prevention in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This study investigated the dental caries rate and related factors of preschool children from Chongming islet in China. The dental caries rate of preschool children in Chongming isket was 45.69%, which was lower than that of children aged 3-5 years in China (62.5%) [9]. By 2020, the global rate of dental caries in primary teeth of children is about 46.2% [10], while the World Health Organization's 2020 global oral health goal is that 80% of children aged 4-5 years are caries free [11].…”
Section: Discussionmentioning
confidence: 90%